Description Of Heart Rate, Respiratory Rate, And Body Temperature Of Haliastur Indus In Kamojang Eagle Conservation Center - Rifqi Akmal Muqsith; Aziiz Mardanarian Rosdianto; Susanti Withaningsih (Media Konservasi, 2023)
Brahminy kite or Halistur indus is one of the protected eagle species in Indonesia. The presence of the eagle in the environment is very important because the eagle is one of many environmental health indicators. Based on the last research of H. indus population in Indonesia, the population of H. indus has decreased due to several factors such as pesticide overuse, destruction of natural habitats, illegal hunting, and illegal trading. Therefore, the conservation programs of H. indus are very important to maintain its population in nature. The purpose of this study is to provide an overview of H. indus’s health including heart rate, respiratory rate, and body temperature who never described on group a group sample in any journal before. The method used in this study was a descriptive method of 15 H. indus in The Kamojang Eagle Conservation Center, Garut, West Java, Indonesia. The result of the heart rate measurement of 15 H. indus obtained the mean and standard deviation was 173.467 ± 11.275 /minute, respiratory rate was 76.400 ± 14.065 /minute, and body temperature was 42.570 ± 0.290 ˚C.